Associations Between Chronic Irritability and Sensory Processing Difficulties in Children and Adolescents - Harima, Yuji; Miyawaki, Dai; Goto, Ayako; Hirai, Kaoru; Sakamoto, Shoko; Hama, Hiroki; Kadono, Shin; Nishiura, Sayaka; Inoue, Koki (Frontiers in Psychiatry, 2022)
Irritability is one of the most common reasons for which children and adolescents are referred for psychiatric evaluation and care. However, clinical irritability is difficult to define; thus, its prevalence varies widely. Chronic irritability may be associated with sensory processing difficulties (SPD), but little is known about the relationship between these two factors in clinical populations. In this study, we examined the prevalence of chronic irritability and its association with SPD in 166 children aged 5–16 years who were referred to the psychiatric outpatient clinic of the Osaka City University Hospital. Chronic irritability and parent-reported scores for the Short Sensory Profile, Infant Behavior Checklist-Revised, Child Behavior Checklist, and Kiddie Schedule for Affective Disorders and Schizophrenia for School-Age Children (Present and Lifetime version) questionnaires were used for assessment. A total of 22 children (13.2%) presented with chronic irritability (i.e., the irritability group) and were more likely to have oppositional defiant disorder, externalizing problems, and attention issues than those without chronic irritability (i.e., the control group). SPD were reported in eight (36%) patients in the irritability group and in 21 (15%) in the control group (p = 0.029). Moreover, compared to the control group, the irritability group showed a significant difference in almost all items of the Short Sensory Profile. Chronic irritability was associated with more severe overall SPD, even after adjusting for possible confounding factors (internalizing and externalizing problems, age, sex, and low income). We provide evidence to support our hypothesis that chronic irritability is associated with SPD in children and adolescents. Therefore, SPD should be assessed to provide appropriate interventions in children and adolescents with chronic irritability.